Advances in immunotherapy for glioblastoma multiforme - Mahmoud, Ahmad Bakur; Ajina, Reham; Aref, Sarah; Darwish, Manar; Alsayb, May; Taher, Mustafa; AlSharif, Shaker A.; Hashem, Anwar M.; Alkayyal, Almohanad A. (Frontiers in Immunology, 2022)
Glioblastoma multiforme (GBM) is the most common and aggressive malignant brain tumor of the central nervous system and has a very poor prognosis. The current standard of care for patients with GBM involves surgical resection, radiotherapy, and chemotherapy. Unfortunately, conventional therapies have not resulted in significant improvements in the survival outcomes of patients with GBM; therefore, the overall mortality rate remains high. Immunotherapy is a type of cancer treatment that helps the immune system to fight cancer and has shown success in different types of aggressive cancers. Recently, healthcare providers have been actively investigating various immunotherapeutic approaches to treat GBM. We reviewed the most promising immunotherapy candidates for glioblastoma that have achieved encouraging results in clinical trials, focusing on immune checkpoint inhibitors, oncolytic viruses, nonreplicating viral vectors, and chimeric antigen receptor (CAR) immunotherapies.